Changes in Patients’ Desired Control of Their Deep Brain Stimulation and Subjective Global Control Over the Course of Deep Brain Stimulation - Merner, Amanda R.; Frazier, Thomas; Ford, Paul J.; Cooper, Scott E.; Machado, Andre; Lapin, Brittany; Vitek, Jerrold; Kubu, Cynthia S. (Frontiers in Human Neuroscience, 2021)
Objective: To examine changes in patients’ desired control of the deep brain stimulator (DBS) and perception of global life control over the course of DBS. A consecutive cohort of 52 patients with Parkinson’s disease (PD) was recruited to participate in a prospective longitudinal study over three assessment points (pre-surgery, post-surgery months 3 and 6). Semi-structured interviews assessing participants’ desire for device control and perception of global control were conducted at each assessment. Qualitative data were coded using content analysis. Visual analogue scales were imbedded in the interviews to quantify participants’ perceptions of control over time. Participants reported significant increases in their perception of global control over time and significant declines in their desired control of the device. These changes were unrelated to improvements in motor symptoms. Improvements in global control were negatively correlated with decline in desired device control. Qualitative data indicate participants have shifting, nuanced levels of desired control over their stimulators. Increased global life control following DBS may be attributed to increased control over PD symptoms, increased ability to engage in valued activities, and increased overall self-regulation, while other domains related to global control remained unaffected by DBS. There are few empirical data documenting patients’ desire for device control over the course of neuromodulation and how device control is related to other aspects of control despite the growing application of neuromodulation devices to treat a variety of disorders. Our data highlight distinctions in different types of control and have implications for the development of patient-controlled neurostimulation devices.